ACCOUNTABILITY COMPETENCE ON INTERNAL AUDIT QUALITY: AUDITORS OF DISTRICT/CITY INSPECTORATES IN WEST JAVA - Aji Wahyu Rosandi; Ade Budi Setiawan; Indra Cahya Kusuma; Didi Didi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This research aims to analyze organizational commitment, auditor motivation, auditor competence and the performance of the government internal audit of audit quality in Inspektorat Kota/Kabupaten Se Jawa Barat. The population in this study is the internal auditor who works in the city/district inspectorate throughout west java. The population is 514 respodents with 226 samples. Sampling used purposive sampling and data analysis using SEM (Structural Equation Model) with PLS application program. The method used by the researcher is quantitative with a causality approach. Data collection was carried out by distributing questionnaires. The results of this study indicate that organizational commitment doesn’t have a direct or indirect effect on audit quality. Motivation doesn’t have a direct effect on audit quality but must go through performance as an intervening variable on audit quality, while auditor competence has direct influence or through performance mediation variables on audit quality. The implication for further research is that variables other than variables that can influence employee performance can be added, such as compensation, work discipline and leadership, as well as taking a sufficient number of research populations.